Pengaruh Work life Balance, Mental Health, Job Insecutiry dan Job Stress Terhadap Turnover Intention pada Generasi Y (Milenial) di Kota Bima - Nurrizah Syaputri; Kartin Aprianti; Jaenab (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effects of work life balance, mental health, job insecurity, and job stress on turnover intention among Generation Y (millennial) employees in Bima City. A quantitative approach with an associative research design was employed. Data were collected through questionnaires distributed to 96 respondents selected using purposive sampling. Multiple linear regression analysis was conducted using SPSS version 27. The findings reveal that work life balance, job insecurity, and job stress have a positive and significant effect on turnover intention, while mental health has a negative and significant effect on turnover intention. Simultaneously, all independent variables significantly influence turnover intention, with a coefficient of determination of 74.3%, indicating that the model explains a substantial proportion of the variance in turnover intention. Job stress was identified as the most dominant factor affecting turnover intention. This study is limited by its focus on respondents in Bima City and the use of cross-sectional data. Future research is recommended to expand the study area and incorporate additional variables such as job satisfaction, organizational commitment, and work environment to provide a more comprehensive understanding of turnover intention